The multifaceted palladium chemistry of 2,2′-diphosphinotolanes - Wagner, Hannah; Ansmann, Nils; Gentner, Timon; Wadepohl, Hubert; Ballmann, Joachim (Organometallics, 2021)
The 2,2′-bis(diisopropylphosphino)tolane 1 was reacted with various palladium precursors to afford a surprisingly diverse array of palladium(II) and palladium(I) complexes. The conventional cationic [PCCP]PdCl+ pincer-type complex 2 was readily obtained by starting from 1 and an in situ generated PdCl+ fragment. Upon chloropalladation of 2 via reaction with a chloride source, a novel vinyl-palladium pincer complex (3) featuring a new C-Cl bond was produced quantitatively. The newly formed C-Cl bond in 3 may be cleaved by addition of AgBF4, which led to the regeneration of 2. Treatment of 1 with (MeCN)2PdCl2 afforded 3 in a single step, while the analogous reaction between 1 and [(η3-allyl)PdCl]2 did not result in chloride or allyl addition. Instead, the alkyne was attacked by one of the phosphines to afford the cationic CArY-MIC palladium complex 4 (CArY-MIC = cyclic (aryl)(ylidic) mesoionic carbene). Upon reaction of 1 with dibenzylidene acetone palladium(0) precursors, two alkynes were coupled to afford the novel palladol 5. When Pd(CNR)2 (R = tBu, Cy) was employed instead of the latter palladium(0) precursors, yet another product was isolated: namely, a dinuclear Pd(I)-Pd(I) complex. In this complex, both palladium atoms are located within the pocket of the ligand and stabilized by isonitrile coligands (CNR with R = tBu for 6a and R = Cy for 6b). The latter isonitriles may be exchanged reversibly for carbon monoxide, as shown by in situ NMR spectroscopy. The finding that five significantly different palladium complexes (2-6) have been isolated by starting from a single phosphino alkyne is discussed in the context of phosphino-palladium-catalyzed alkyne transformations.